The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.48295/et.2021.81.7
|View full text |Cite
|
Sign up to set email alerts
|

Development of congestion index model and analysis of mitigation measures on urban arterials using microsimulation

Abstract: Traffic congestion is one of the main issues related to traffic engineering, planning, and policies that directly influence the economy, environment, and lifestyle in developing countries, particularly in India. This study's main objectives are to establish the congestion index model and analyze the various mitigation measures using microsimulation. The required data were collected from selected two corridors in Tiruchirappalli, India. A correlation test was performed to identify the significant parameters tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The simulation results showed that SPUI's overall performance is better than TUDI's in all transportation parameters. Akshara and Marisamynathan (2021) obtained traffic data by conducting a video graphic survey from two selected corridors in Tiruchirappalli, India, during weekday peak and off-peak hours. By modeling traffic congestion in the VISSIM microsimulation program, they simulated suggestions to reduce traffic congestion in possible scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results showed that SPUI's overall performance is better than TUDI's in all transportation parameters. Akshara and Marisamynathan (2021) obtained traffic data by conducting a video graphic survey from two selected corridors in Tiruchirappalli, India, during weekday peak and off-peak hours. By modeling traffic congestion in the VISSIM microsimulation program, they simulated suggestions to reduce traffic congestion in possible scenarios.…”
Section: Introductionmentioning
confidence: 99%